West Africa security perspectives: Kwesi Aning explains - Kwesi Aning; Peter Albrecht; Anne Blaabjerg Nielsen (Danish Institute for International Studies (DIIS), 2021)
In the autumn of 2020 professor and director of the Kofi Annan International Peacekeeping Training Centre, Kwesi Aning, visited DIIS. He has had a long career in both academia and policymaking with the African Union and the United Nations, and he has written extensively on security dynamics and politics across West Africa. This report is the product of several structured conversations between Aning and researchers at DIIS in Copenhagen, which have been edited into eight texts that discuss key security challenges and megatrends in contemporary West Africa, ranging from illegal mining and organized crime to international interventions and piracy. One of Aning's points is that the West African states are in crisis - more so than in the early years of the post-Cold War era. A key reason for this is popular disappointments in the face of economic inequality; reversals in the application of democratic principles; a demographic boom; and climate change resulting in environmental disasters and degradation. Together, these factors compound the failure of states to maintain optimism and live up to the expectations of their populations. Countries from outside the region that make the decision to intervene, and that design the interventions, must have a fundamental understanding of the contexts in which they intervene and of their own limitations. Only then will external actors be able to support further steps taken in the region to mitigate some of the challenges that West Africa faces, challenges which have led to conflict in the past, and may lead not just to new and renewed conflicts, but also to the spread of existing ones.
Keywords: 300